ANALISIS SUHU UDARA, KELEMBAPAN UDARA, DAN TEKANAN UDARA TERHADAP CURAH HUJAN (STUDY KASUS : KOTA SERANG) - Mila Nuridhati; Ruhiat, Yayat; Guntara, Yudi (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to analyze the impact of air temperature, air humidity, and air pressure on rainfall, both individually and simultaneously. The method applied is multiple linear regression, with secondary data for 5 years from 2019 to 2023. The results showed that air humidity, air pressure, and minimum air temperature have a positive influence on rainfall, while maximum air temperature has a negative influence. Simultaneously air humidity, air pressure, minimum temperature, and maximum temperature together have a significant effect on rainfall by 55,6%. However, artially, only the minimum air temperature has a significant effect, while the variables of maximum air temperature, air humidity, and air pressure do not show a significant effect.